Association of F2-isoprostane levels with Alzheimer’s disease in observational studies: a systematic review and meta-analysis - Trares, Kira; Chen, Li-Ju; Schöttker, Ben (Ageing research reviews, 2022)
Introduction - The association between F2-isoprostanes and Alzheimer’s disease (AD) has been controversially discussed in the literature since the 1990s. However, no systematic review has been performed so far. - Methods - A systematic review of observational studies on the associations of F2-isoprostanes and the specific biomarker 8-iso-prostaglandin F2α with AD were conducted. Random-effects model meta-analyses were performed. - Results - 29 studies were included in the systematic review, including four longitudinal studies. In an overall meta-analysis of the 25 cross-sectional studies, F2-isoprostane levels were statistically significantly associated with AD (Hedge’s g [95% confidence interval]: 1.00 [0.69-1.32]). When studies were grouped by biomarker and sample specimen, F2-isoprostane and 8-iso-prostaglandin F2α levels were statistically significantly elevated in tissue samples of the frontal lobe of AD patients. Moreover, F2-isoprostane levels in cerebrospinal fluid and 8-iso-prostaglandin F2α levels in blood samples of AD patients were significantly increased. Meta-analyses of the few longitudinal studies did not reach statistical significance. - Discussion - Increased concentrations of F2-isoprostanes were found in AD patients. However, due to the lack of adjustment in most cross-sectional case-control studies, results must be interpreted carefully. In addition, the causality of the association is uncertain because evidence from well-conducted longitudinal studies was conflicting, and further longitudinal studies are required to reinforce the results.
Im Text ist "2" tiefgestellt
Available online 24 December 2021
Gesehen am 20.05.2022